STRATEGI PEMBELAJARAN KONTEKSTUAL BAGI GENERASI Z DAN ALPHA: INTEGRASI NILAI KARAKTER DAN TEKNOLOGI - Anugrah Agung; Muhammad Habib Ramadhani; Irfan Supriatna; Putera, Rafhi (Prosiding Temu Ilmiah Nasional Guru, 2026)
Generational shifts have brought new challenges to the field of education. Generation Z and Generation Alpha possess unique characteristics, including their closeness to technology, multitasking abilities, and a strong need for practical and meaningful learning experiences. These traits demand innovative learning strategies that not only integrate technology but also foster character development. This study aims to explore contextual learning strategies that integrate character values and digital technology to create relevant and meaningful learning for Generation Z and Alpha. Using a qualitative descriptive approach through literature review and observation, the research identifies that contextual learning—when combined with digital-based interactive media—enhances learning engagement, strengthens character education, and promotes critical and creative thinking skills. The findings reveal that students are more motivated when learning is connected to real-life contexts and supported by technological tools. Furthermore, integrating moral values such as responsibility, honesty, and empathy within digital learning environments helps shape balanced and ethical learners. In conclusion, contextual learning that harmonizes character education and technology provides an effective model for 21st-century education, preparing young generations to be critical, innovative, and morally grounded individuals.